(untitled) (Research, Society and Development, 2021)
The continuous interference of human activities in continental aquatic systems results in direct and indirect impacts, with consequences for water quality, aquatic biota and the dynamics of water resources. In this context, the Tucuruí Hydroelectric Power Plant (HPP) acquired relatively importance, as it was the first large dam carried out in the Amazon, in the 1980s, presenting important technical/economic results to justify the environmental costs associated with the project. The objective of this study was to apply a new methodology to represent through maps georeferencing biological information and evaluate the impact of the dam on the following fish species, which have different physiologies and taxonomies, in addition to not having much biological information about the species: Botinho (Hassar wilderi, Doradidae), Mandubé (Ageneiosus ucayalensis, Auchenipteridae), Sardinha Papuda (Triportheus trifurcatus, Characidae) and Uéua Cachorrinho (Acestrorhynchus falcirostris, Acestrorhynchidae). The condition factor related to the relationship between the individual’s weight and body length, which derives from an expansion of the cubic law of living beings, being very important in ecological studies, even though they depend on simple to the most complex scientific methods, to estimate this bodily condition. Furthermore, this biological parameter influenced by environmental conditions and characteristics, due to food availability and ecological relationships in the environment. This information can support an adequate fisheries management, as there is an integration of fisheries biology and the characteristics of the environment in which they live. Thus, the methodology applied in this study was successful in its application proposal.